Analysis of Logistics Cost on Smallholder and Middleman to Foster Tea Supply Chain: A Case Study in Central Java Province, Indonesia - Hu Bai; Megita Ryanjani Tanuputri (agriTECH, 2022)
The competitiveness of Indonesian tea in the global market is diminishing due to the oversupply and inability to provide agile logistics and market-oriented quality. Therefore, this study aims to evaluate the current tea supply chain and analyze the logistics cost based on the activity-based costing (ABC) method in the smallholder and middleman tier to foster the sustainability of tea agribusiness. It was conducted in three main areas in Central Java Province, Indonesia, namely Batang, Pekalongan, and Banjarnegara regency. The method used was an in-depth interview and a semi-structured questionnaire to gain holistic information from 181 respondents. The results showed that material handling activity and transportation have the highest portion of the smallholder’s and middleman logistics costs, respectively. The total logistics cost of smallholders varied from case to case, ranging from IDR 821.7 to IDR 1,075.0 per kg of fresh tea leaves. Transportation activity and administration costs make up 30.8% of the total smallholder’s logistics cost. Meanwhile, the current development of the global tea market promotes policy adaptation on the commercial plantation tier and increases the cost of labor for plucking activity up to 2.5 times. Additionally, this study discovered the profit range of smallholders and middlemen. Therefore, the collaborative work of all parties is necessary to succeed in sustainable tea agribusiness.